Temperature alert alarm system (TAAS) - Norhidayah, Masstor (2015)
This paper presents the implementation of the Temperature Alert Alarm System which is used for environmental monitoring using heat sensors. The current situation in Malaysia, especially in Universiti Malaysia Pahang, Gambang Campus is that the weather is unpredictable and can be unstable. According to the Deputy Dean for Academic Affairs, Student Affairs and Alumni, Industry and Community, Faculty of Environmental Studies, Universiti Putra Malaysia (UPM) Associate Professor Dr Ahmad Makmom Abdullah said despite the lack of water occurs within a short period, it is still considered as the dry season. He also said that climate change in Malaysia was based on the annual pattern when the arrival of February, the changes of monsoon season will occur. According to Dr Makmom, warm weather experienced during this is due to lack of wind emission from Sumatra as well as volcanic eruptions are quite active in Indonesia. It is recorded in the Metro newspaper dated 2 February 2014. Therefore, this work would like to propose a monitoring mechanism that takes reading samples at constant rates throughout its operation. The aim is to design a system that evaluates samples only when it is triggered by an outside event, especially hot air and winds that have probability to result of fire forest occurs. The objective of this paper is to develop an embedded sensor of heat detector to alert residence the certain area about the hot dry weather. The embedded sensor that will be mechanism developed has variable sampling rates with interfaces to temperature sensor. The developed system would provide an applicable device that can be used in Universiti Malaysia Pahang as an organised weather and environmental forecasting system.